1987
DOI: 10.1111/j.1439-0450.1987.tb00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of a Dermonecrotic Crude Toxin Preparation from Pasteurella multocida Serotype D in Rats

Abstract: Summary Following systemic application of dermonecrotic crude toxin (DNT) from a sonic extract of Pasteurella multocida type D into 20 young adult male rats, its distribution and time dependence as well as the toxin induced organ alterations were studied. In all animals, liver, kidney, spleen, lymph nodes, thymus, cross‐sections of the nose, duodenum, gastric wall, lung, and adrenal gland were excised, fixed, dehydrated and embedded in glycol methacrylate. The immunoperoxidase‐avidin‐biotin‐complex‐technique w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Lesions in our rats were similar to those in studies where toxin was detected in Kupffer cells and leukocytes using immunoperoxidase, avidin-biotin techniques. 21 Endogenous bacterial endotoxins in the portal venous system of the rat probably contribute to liver damage.15 Lipopolysaccharides and Lipid A, even at low doses, markedly reduce hepatobiliary clearance of leukotrienes. Kupffer cells, like macrophages, engulf endotoxin by endocytosis and subsequently release ar- achidonic acid metabolites, cytokines, procoagulants, fibronectin, lysosomal enzymes, and other factors which are vasoactive, chemoattractant, or toxic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesions in our rats were similar to those in studies where toxin was detected in Kupffer cells and leukocytes using immunoperoxidase, avidin-biotin techniques. 21 Endogenous bacterial endotoxins in the portal venous system of the rat probably contribute to liver damage.15 Lipopolysaccharides and Lipid A, even at low doses, markedly reduce hepatobiliary clearance of leukotrienes. Kupffer cells, like macrophages, engulf endotoxin by endocytosis and subsequently release ar- achidonic acid metabolites, cytokines, procoagulants, fibronectin, lysosomal enzymes, and other factors which are vasoactive, chemoattractant, or toxic.…”
Section: Discussionmentioning
confidence: 99%
“…' Although not commonly recognized in natural disease, pasteurella toxins (PT) also produce important systemic effects, including damage to liver and kidney.6J1 Experimentally, degeneration of hepatocytes has been reported (but not characterized) in piglets given toxin intraperitoneally (250 pg) 22 and by aerosol (125 pg).6 A PT (which also contained endotoxin), when given intradermally to rats, caused "dystrophic alterations" in liver, kidney, adrenal cortex, and lymphoid tissues. 21 Recently we have shown that PT given subcutaneously causes acute cell swelling and necrosis of hepatocytes in pigs.3 Although not adequately documented, these lesions suggest that toxins may cause alterations of vascular tissue or in systems that control metabolism in liver, skeletal muscle, or kidney. Hepatocytes, through production of acute phase proteins of inflammation, have the capacity to reduce growth, particularly of muscle tissue.…”
mentioning
confidence: 99%